The Effect of Tariffs in Global Value Chains - Eugster, Johannes (IMF Working Papers; Working Paper ;, 2022)
This paper empirically investigates the impact of tariffs when production is organized in global value chains. Using global input-output matrices, we construct four different tariff measures that capture the direct and indirect exposure to tariffs at different stages of the production chain for a broad set of countries and industries. Our results suggest that tariffs have significant effects on economic outcomes, including on countries and sectors not directly targeted. We find that tariffs higher up and further down in the value chain depress value added, employment, labor productivity and total factor productivity to varying degrees. We find no benefits for the sector that enjoys additional protection, yet there is some evidence of economic activity being diverted, id est positive effects on value added and employment from tariffs imposed on competitors. Our paper relates to recent innovations in theoretical gravity models and provides an empirical assessment of possible long-term effects of recent trade tensions.